Saccharomyces cerevisiae, Non-Saccharomyces Yeasts and Lactic Acid Bacteria in Sequential Fermentations: Effect on Phenolics and Sensory Attributes of South African Syrah Wines - Minnaar, P.P.; du Plessis, H.W.; Paulsen, V.; Ntushelo, N.; Jolly, N.P.; du Toit, M. (South African Journal of Enology and Viticulture, 2017)
Wine consumers predominantly use visual, sensory and textual descriptors as quality/preference indicators to describe olfactory sensations. In this study, different wines were analysed to generate relevant chemical and sensory characterisation data and attributes. Sequential inoculation of Syrah grape must was performed with a combination of Saccharomyces yeast, non-Saccharomyces yeasts and lactic acid bacteria for the possible improvement of Syrah wine quality. Selected anthocyanins, flavan-3-ols, flavonols and phenolic acids were quantified in Syrah wines using the reversed-phase high-performance liquid chromatography photodiode array detection (RP-HPLC-DAD) technique. Sensory (descriptive evaluation) and physicochemical/oenological parameters (Winescan® and OenoFoss™) results were compared to phenolic compound concentrations. Phenolic compound concentrations increased in Syrah wines made with a combination of a Saccharomyces reference yeast, non-Saccharomyces yeasts and lactic acid bacteria. Syrah wines made with a combination of Metschnikowia pulcherrima + Saccharomyces cerevisiae + Oenococcus oeni, and M. pulcherrima + S. cerevisiae + Lactobacillus plantarum, had higher flavonol concentrations compared to wines made without lactic acid bacteria. Syrah wines made with a combination of Saccharomyces cerevisiae (Sc) + Oenococcus oeni (LAB1) were highest in phenolic acid concentrations. Syrah wines made with a combination of M. pulcherrima + S. cerevisiae + L. plantarum had higher total anthocyanins than wines made without lactic acid bacteria. Syrah wine sensory attributes, viz. mouthfeel and astringency, correlated with a combination of lactic acid bacteria and yeast treatments. Syrah wines made with a combination of yeast and lactic acid bacteria (LAB) scored highest in overall quality. Indications are that the S. cerevisiae reference yeast retained more phenolic compounds during fermentation when compared to wines made with a combination of non-Saccharomyces yeasts and LAB. The improved red colour of Syrah wines may be achieved by sequential inoculation with non-Saccharomyces yeast and LAB. This could be beneficial where winemakers use grape cultivars with low anthocyanin levels in the grape skin to produce wines of improved quality.